Cisco wireless LAN security - Sankar, Krishna; Sujdaralingam, Sri; Balinsky, Andrew; Darrin, Miller (Indianapolis, IN : Cisco Press, 2005)
A guide to wireless LAN technology and security, covering such topics as protocols, deployment patterns, WEP, EAP, switching, and management.
"Expert guidance for securing your 802.11 networks"--Cover.
Includes bibliographical references and index.
rua 28/10/13
Loans
Keywords: Wireless LANs; IEEE 802.11 (Standard)